THE QUICKSCREEN TOOL—A VALIDATED FALLS RISK ASSESSMENT, DEVELOPED AND IMPLEMENTED IN AUSTRALIA FOR USE IN PRIMARY CARE. (7th October 2012) - Tiedemann, A; Lord, S; Sherrington, C
Abstract : Background: Falling in older age presents a major challenge to health systems and older people. This abstract forms part of the symposium: 'Integrating Older Adult Falls Prevention into Clinical Practice—Experiences from Four Countries', which also includes presentations by Judy Stevens, Clare Robertson and Vicky Scott. Aims/Objectives/Purpose: We will outline the development of the QuickScreen risk assessment, including the validation, reliability and feasibility studies and implementation into practice. Methods: The development study involved 764 older community-living people. 362 people participated in the external validation and 30 in the reliability study. The QuickScreen was trialled by 32 clinicians with their patients. Results/Outcome: 20% of development study participants experienced multiple falls (≥2) during the 1-year follow-up. Each of the assessment items; low-contrast visual acuity, tactile sensitivity, sit to stand test, alternate step test, near tandem stand test, previous falls and medications, discriminated between multiple fallers and non-multiple fallers (relative risk values: 1.4–2.4). 22% of external validation study participants suffered multiple falls during the prospective follow-up and the QuickScreen discriminated between falls groups with an area under the ROC curve of 0.72 (95% CI 0.66 to 0.79). The QuickScreen items exhibited moderate to excellent test–retest reliability (intra-class correlation coefficients range: 0.54–0.89). 72% of the clinicians found that the assessment took less than 10 min to administer, making it feasible for use in a normal consultation time. Significance/Contribution: The QuickScreen can identify high-risk fallers and help to guide fall-prevention interventions. It has been implemented in Australia and internationally by a range of health professionals.